Fitness benefits to intrasexual aggression in female house wrens, Troglodytes aedon. (February 2020) - Krieg, Cara A.; Getty, Thomas
Abstract : Males frequently compete for access to mates, sometimes at a cost to parental behaviour and self-maintenance. Theory predicts that aggressive competition among females should be less common and intense due to a trade-off between competition and future reproductive investment. However, the consequences of female aggression across the reproductive cycle are unknown in many species. In this study, we addressed four questions about female intrasexual aggression in the house wren. (1) Does intrasexual aggression help females during periods of increased competition over breeding resources? (2) Do aggressive females have higher-quality mates? (3) Do aggressive females invest less in reproduction? (4) Does female aggression affect offspring size and survival? We experimentally increased competition over nestboxes in one year by evicting a subset of birds. Females that were more aggressive during previous simulated female intrusions protected more eggs from house wren ovicide, which increased following our manipulation. In two other years, we monitored the mating patterns and reproductive performance of females. Aggressive females had mates that provided more direct benefits in the form of nestling provisioning. They did not invest less in reproduction and, in fact, provisioned their nestlings more frequently. As a result, aggressive females had heavier offspring at multiple points during development. The offspring of more aggressive females were also more likely to fledge. Overall, female aggression appeared to have fitness benefits directly following an experimental increase in competition and throughout the reproductive cycle in nonexperimental years. Highlights: Aggressive females protected more eggs from ovicide during increased competition. They did not invest less in egg production. Aggressive females and their mates provisioned offspring more frequently. Offspring of more aggressive females were larger at multiple points in development. They were also more likely to fledge.